2018
DOI: 10.1177/1350650118818303
|View full text |Cite
|
Sign up to set email alerts
|

Influence of local turbulent flow on the performance of a mixed-lubrication bearing

Abstract: For some large heavy load bearings, asperity contact may occur in the area near the minimum film thickness. However, in the remaining area, the liquid film may be much thicker, and thus turbulence develops locally. To investigate the influence of local turbulent flow on the performance of a mixed-lubrication bearing, in this paper, the bearing is divided into a mixed-lubrication region and a pure hydrodynamic lubrication region according to the film thickness ratio. The liquid in the mixed-lubrication region i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Re l and Re t represent the critical number for laminar and turbulence flow, 31 respectively. Considering its specific flow characteristic of LOX in micron clearance, Re l and Re t are selected as 900 and 1360, respectively.…”
Section: Superconducting Magnetic Levitation Forcementioning
confidence: 99%
“…Re l and Re t represent the critical number for laminar and turbulence flow, 31 respectively. Considering its specific flow characteristic of LOX in micron clearance, Re l and Re t are selected as 900 and 1360, respectively.…”
Section: Superconducting Magnetic Levitation Forcementioning
confidence: 99%
“…Liu et al [ 10 ] considered the effect of elastic deformation on the lubrication state of water-lubricated bearings and analyzed the variation of parameters such as maximum pressure value and minimum oil film thickness under different bearing clearance structures. Lv et al [ 11 , 12 ] indicated that large bearings’ maximum oil film thickness was much greater than the minimum nominal oil film thickness, and local turbulence might occur. Results of calculations by the finite-difference method also showed that turbulence significantly affected the bearing friction coefficient and the minimum oil film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, in terms of laminar turbulence, Lv [19,20] studied the influence of local turbulence on the mixed lubrication performance and bearing stability of large heavy-duty bearings, and the results also showed that local turbulence had a significant impact on the friction coefficient. Zhu [21] solved the generalized turbulent Reynolds lubrication equation and energy equation, and obtained the influence of journal tilt and journal surface roughness on journal bearing lubrication performance.…”
Section: Introductionmentioning
confidence: 99%